Analisis Kualitas Layanan Website Terhadap Kepuasan Mahasiswa dengan Penerapan Metode Webqual (Studi Kasus : UIN Suska Riau) - siti mona lisa (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2016)
Based on observations, many update some information that is not carried by the website manager UIN Suska such facilities are still blank menu, menu student, and some information about the update such as academic calendar, academic guide on the website UIN Suska Riau.Untuk produce satisfactory service quality value then the lending institutions of services in this regard UIN Suska must measure the quality of service based on customer tastes and not according to taste providers. The results of the study explained that the quality of service is only able to explain the relationship of student satisfaction at 0.354 which means the quality of the service is only able to explain directly to the satisfaction of 35.4%. While the rest of greater value that is 64.6% explained by other variables that are not described in this study. Based on the t variable with the usability of 0.297 t sebesar1,664 table does not have a significant relationship to student satisfaction variables, variable information quality amounted to 1.144 t sebesar1,664 table does not have a significant relationship to student satisfaction variables and variable quality interaction by 3.651 with t table sebesar1,664 have a significant relationship to the satisfaction variables. Quality of service Website dominant influence on students satisfaction is interaction quality is variable, namely 0467.